(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
إن الهدف من هذا العمل هو دراسة الزمرة البوليانية المنتهية والتي تعرف بأنها الزمرة التي فيها كل عنصر x رتبته 2 ، وقد أثبتنا أن رتبة الزمرة البوليانية المولدة بـ n عنصراً هي , سنرمز للزمرة البوليانية من الرتبة بالرمز , كما أثبتنا أن كل زمرة بوليانية من الرتبة ايزومورفية مع الزمرة . وفي هذه الحالة فإن كل عنصر من عناصر الزمرة البوليانية يمكن التعبير عنه كمتتالية من n مركبة عناصرها من , وبينّّا كذلك أن كل زمرة بوليانية هي زمرة مرتبة بعملية ترتيب ثم إن كل زمرة بوليانية هي شبكة مع العمليتين إثبات أنها شبكة بوليانية . The purpose of this paper is to study the finite Boolean group which is known as the group in which every element x has order 2. We proved that the Boolean group order was generated by n elements is . We refer to the Boolean group from order as . In addition, we proved that every Boolean group from order was an isomorphism with the group . So, in this situation every element of the Boolean group can be represented as a sequence of n projection whose elements are of . We also showed that the Boolean group is an organized group by the order operation. Thus, every Boolean is a lattice with two operations . This proves that it is a Boolean lattice.